2007
DOI: 10.1007/s00787-006-0584-x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood depression: a place for psychotherapy

Abstract: This study provides evidence supporting the use of focused forms of both Individual Psychodynamic Therapy and Family Therapy for moderate to severe depression in children and young adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 23 publications
2
57
1
1
Order By: Relevance
“…76 The STPP method 73,77 draws on a long history in the UK of psychoanalytic work with depressed children and young people, 77,78 including an earlier clinical trial, in which STPP for children with depression demonstrated good outcomes. 35 As with the other manuals used in IMPACT, the STPP manual 74 provided a guide to practice but not a recipe or a step-by-step guide, and drew on the existing skills and training of child and adolescent psychotherapists already working in the NHS.…”
Section: Short-term Psychoanalytic Psychotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…76 The STPP method 73,77 draws on a long history in the UK of psychoanalytic work with depressed children and young people, 77,78 including an earlier clinical trial, in which STPP for children with depression demonstrated good outcomes. 35 As with the other manuals used in IMPACT, the STPP manual 74 provided a guide to practice but not a recipe or a step-by-step guide, and drew on the existing skills and training of child and adolescent psychotherapists already working in the NHS.…”
Section: Short-term Psychoanalytic Psychotherapymentioning
confidence: 99%
“…At the time of starting Improving Mood with Psychoanalytic and Cognitive Behaviour Therapy (IMPACT), it was standard practice (in keeping with NICE guidelines) to start treatment with specific psychological therapy. In addition, unlike prior UK RCT studies, 12,35 we added potential moderators of recurrence risk and relapse rates. These were individual differences in (1) self-reported rumination (persistently brooding or dwelling, often to the exclusion of other themes in the patient's life) 36,37 and (2) depressive thinking style (the extent to which patients with clinical depression may be characterised in terms of immaturity of the cognitive styles of self-criticism and perfectionism).…”
mentioning
confidence: 99%
“…However one conclusion that has already been drawn from clinical experience of delivering it (and from a previous study Trowell (2012), is that not only may a fixed term of once-weekly treatment for a year not be harmful, compared with treatments without a predefined ending, but that it may even be beneficial especially to adolescent patients.It seems likely that training in time-limited therapy will now be added to the training requirements of the child psychotherapy profession. Should this trial prove successful in terms of treatment outcomes, it seems likely that NICE will take a much more favourable view than hiitherto of the value of psychoanalytic treatment at least for severe depressive illness.…”
Section: The Programme Of This Conference Gives Considerable Emphasismentioning
confidence: 99%
“…The capacity of attachment models to explain and indeed predict patterns of development, including across generations, has been amply demonstrated. The literature on the outcomes of psychoanalytic psychotherapy with children and adolescents (Kennedy 2004, Kennedy and Midgley 2007, Trowell 2012) also indicates, that these methods achieve considerably better outcomes than routine psychiatric treatments. 4 The fact that these results can be achieved by practitioners from different therapeutic schools does not invalidate their theories, since therapists from different schools of psychoanalysis share many fundamental assumptions.…”
Section: Commentarymentioning
confidence: 99%